The Effect of Training and Safety Knowledge on Crew Competence and its Implications for Occupational Safety Onboard at PT. Gelora Persada Makmur - Megi Krisma Atamimi; Anditalin Anggraeni; Abdul Rachman; Marihot Simanjuntak; Susi Herawati; Arika Palapa (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the effect of safety training and safety knowledge on crew competence and its implications for occupational safety on board ships at PT. Gelora Persada Makmur. This research employs a quantitative research design using a survey method with a cross-sectional approach. The population of this study consists of all ship crew members of PT. Gelora Persada Makmur, totaling 100 respondents. A saturated sampling technique was applied, in which the entire population was used as the research sample. Data were collected through a closed-ended questionnaire using a five-point Likert scale distributed online. The collected data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results of this study are expected to indicate that safety training and safety knowledge have a positive effect on crew competence, both directly and indirectly, and that crew competence has a positive effect on occupational safety on board. These findings are expected to serve as a basis for improving operational safety management within the company